Static performance of steel temcor joint subjected to out-of-plane bending moments. (May 2022) - Mashrah, W.A.H.; Chen, Zhihua; Liu, Hongbo; Boufendassa, Rima; Mogalli, Abdullah
Abstract: The temcor system is one of the most famous single-layer grid shell structures' connections. In this study, temcor joints were designed using Q345 steel with Huck bolts instead of the aluminium alloy to expand using an H-shaped beam of steel in single-layer grid shell structures. Twenty-two joints with a single Huck bolt connection were designed and tested to investigate the shear strength of Huck bolts. At the same time, three specimens of steel temcor joint (TC1, TC2, and TC3) were designed considering the number of Huck bolts, the thickness of the gusset plates, and material type. FE models for tested joints were established using Abaqus to conduct numerical and parametrical analyses. The experimental and numerical results indicated that the bending capacity and the stiffness of the steel temcor joint were limited increased by increasing the gusset plate thickness. However, when the thickness of gusset plates exceeded the thickness of the flanges of the H-shaped beam, the main failure occurred on the H-shaped beam. However, those joints' stiffness and bending capacity stopped increasing. Moreover, the bending capacity and stiffness of steel temcor joints were higher than that of aluminium temcor joints by an average of 177% and 180%, respectively. The theoretical solution for the bending capacity of steel temcor joint was proposed, and their stiffness was calculated based on Eurocode 3. Finally, the bending capacity and stiffness of the temcor joints obtained from FE models and theoretical equations were in good agreement with the experimental data.